A Comparative Analysis of Lexical Variation of Verbs in Minangkabau and Banjar Languages: Historical Comparative Linguistic Study - Amri, Ulil; Putra, Yoga Mestika; Putri, Aprilia Kartika; Triandana, Anggi; Fitriah, Siti (English Department, Faculty of Humanities, Andalas University, 2024)
The aim of this research is to analyze lexical variations of isolects in Banjar and Minangkabau languages and to calculate the relationship percentage of the two languages. The method used in this research is a comparative method with a qualitative and quantitative approach to find phonemic and lexical correspondences of the relative lexemes. The data consists of 115 action verbs (glosses) at four observation points of Minangkabau language and two observation points of Banjar language. The data was collected by using non-participation method through notetaking and recording techniques. The Lexicostatistic calculation method is used to calculate inter-language relationships. The results of the analysis show that there were 265 total lexemes of 241 etymons with: 9 cognate (exact-similar), 79 inheritance (minimal-pairs), and 182 different variations of lexemes (considered as borrowing and by chance). The result of the lexicostatistic calculation indicates that the two languages are related by 66.38% and is classified as languages in the same language based on 116 verbs analyzed.